2018
DOI: 10.3389/fphar.2018.00347
|View full text |Cite
|
Sign up to set email alerts
|

Root Extract of Polygonum cuspidatum Siebold & Zucc. Ameliorates DSS-Induced Ulcerative Colitis by Affecting NF-kappaB Signaling Pathway in a Mouse Model via Synergistic Effects of Polydatin, Resveratrol, and Emodin

Abstract: Background: Polygonum cuspidatum Siebold & Zucc. (PCS) has antibacterial properties and may prevent Ulcerative colitis (UC) but related molecular mechanism remains unknown. NF-κB signaling pathway is associated with inflammatory responses and its inactivation may be critical for effective therapy of UC.Methods: UC mouse (C57BL/6J) model was established by using dextran sulfate sodium (DSS). The extract of PCS (PCSE) was prepared by using ethanol and its main ingredients were measured by HPLC. Thirty-two UC mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Highly localized concentrations of ROS could attack and inactivate endogenous antioxidant defenses, such as GSH-Px, T-SOD, and CAT, thus preventing the neutralization of ROS [32, 33]. We also observed a decrease in colonic GSH-Px, T-SOD, and CAT activities in DSS-treated mice compared with those in the control mice, which were consistent with previous reports [32, 34]. Notably, administration of QD significantly restrained the elevation of colonic MPO activity and decreased colonic GSH-Px, T-SOD, and CAT activities in DSS-treated mice.…”
Section: Discussionsupporting
confidence: 92%
“…Highly localized concentrations of ROS could attack and inactivate endogenous antioxidant defenses, such as GSH-Px, T-SOD, and CAT, thus preventing the neutralization of ROS [32, 33]. We also observed a decrease in colonic GSH-Px, T-SOD, and CAT activities in DSS-treated mice compared with those in the control mice, which were consistent with previous reports [32, 34]. Notably, administration of QD significantly restrained the elevation of colonic MPO activity and decreased colonic GSH-Px, T-SOD, and CAT activities in DSS-treated mice.…”
Section: Discussionsupporting
confidence: 92%
“…Xu et al [ 27 ] have shown that PD suppresses the secretion of proinflammatory cytokines, including TNF- α , IL-1 β , and IL-6, into the circulation. The available literature has indicated that the anti-inflammatory effects of PD may be attributed to its ability to prevent the overactivation of nuclear factor-kappa B (NF- κ B) signals, as this signaling pathway is responsible for regulating the transcription of proinflammatory mediators during immunological stress [ 10 , 38 , 39 ]. Support for an inhibitory effect of PD on NF- κ B signals has been provided by Wu et al [ 24 ], who observed that PD decreased the DNA binding ability of NF- κ B p65 during intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…(PCS) treatment can prevent DSS-caused weight loss and colon length reduction in UC mice, as well as increase the serum levels of IL-10 and reduce the levels of IL-1β, IL-6 and TNF-α. Moreover, whatever PCSE (100, 200 and 400 mg/kg) or the combination of its three extractions: polydatin, resveratrol and emodin exhibit higher inhibitory activities for cytokines and NF-κB signaling related molecules than any one of the three compounds with same concentration treatment [64].…”
Section: Heat-clearing and Dampness-drying Medicinementioning
confidence: 94%